The influence of service quality on customer satisfaction: a study on frame check service at PT Daya Adicipta Motora Bandung - Ade Oki Pebiansyah; Gumi Gumilang Wirakanda; Ervie Nur Afifa M; Ajeng Oktaviani (Enrichment : Journal of Management, 2026)
The fierce competition in Indonesia's automotive sector compels businesses to focus on after-sales services alongside vehicle sales to maintain customer satisfaction and loyalty. While previous studies have extensively explored general service quality, there remains a prominent research gap regarding its integration with specific voucher-based incentive programs in motorcycle after-sales services. Addressing this gap, the novelty of this study lies in its specific examination of the Frame Check Service (LCR) program at PT Daya Adicipta Motora in Bandung, evaluating how targeted service quality dimensions influence customer satisfaction. A quantitative approach was employed using a survey method with a five-point Likert-scale questionnaire. The sample comprised 74 respondents, calculated via the Slovin formula, and data were analyzed using simple linear regression, along with validity and reliability tests in SPSS version 27. The findings indicate that customer satisfaction is strong, with an average score of 4.14, and service quality is assessed as very high, with an average score of 4.25. Empirical regression outputs reveal that service quality exerts a statistically significant positive effect on customer satisfaction, evidenced by a coefficient of 0.935 and a constant of 9.134. Furthermore, the coefficient of determination (R²) of 45.5% represents the model’s ability to explain the variation in customer satisfaction, with the remaining variance attributable to other factors such as cost, promotions, and overall service experience. This study contributes to the service management literature by providing empirical evidence on the dynamics between specialized service programs and consumer satisfaction. Practically, the findings suggest that businesses should enhance customer retention strategies, improve the convenience of service locations, and develop long-lasting loyalty programs